(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2021)
The developing world invites Foreign Direct Investment (FDI) to their countries nearly unconditionally for the developmental benefits. However, in literature there are concerns regarding ‘unfettered FDI’ in terms of several factors including FDI outflows which contribute to Current Account Deficits. This paper investigates the relationship between FDI and profit outflows on the case of Turkey via economic causality analysis through Granger causality test using a method developed by Toda and Yamamoto (1995) and the impulse-response analysis. The results indicate that although there are short-term positive effects of FDI inflows in terms of current account financing, the causality results point to the long-term adverse effects of FDI inflows on profit remittance leading to current account deficit, which is an issue that policy makers should consider when trying to attract FDI.